2017
DOI: 10.1002/iub.1637
|View full text |Cite
|
Sign up to set email alerts
|

A putative association of interleukin‐10 promoter polymorphisms with cardiovascular disease

Abstract: Interleukin-10 (IL-10) is an anti inflammatory cytokine involved in the ongoing coronary inflammation and related patho-physiological processes. The piece of work presented herein is aimed at investigating possible association of polymorphisms in IL-10 promoter with Saudi cardiovascular disease (CVD) patients. The study included 80 confirmed CVD patients with diabetes and 75 healthy control individuals both men and women. Concentration of IL-10 in the serum samples were measured by ELISA method. For single nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
0
19
0
2
Order By: Relevance
“…In a self-stimulating loop, the microglia can also secrete IL-12, activating NK and stimulating T cells 52 . IL-10 is a multifunctional immune cytokine with anti-angiogenic properties 53,54 . Finally, cytokines like IL-1β and TNFα can suppress tumors via stimulation of cell-mediated humoral immune reaction 55 .…”
Section: Discussionmentioning
confidence: 99%
“…In a self-stimulating loop, the microglia can also secrete IL-12, activating NK and stimulating T cells 52 . IL-10 is a multifunctional immune cytokine with anti-angiogenic properties 53,54 . Finally, cytokines like IL-1β and TNFα can suppress tumors via stimulation of cell-mediated humoral immune reaction 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported a mean 6 SD serum IL-10 level of 34.4 6 38.5 pg/ml (34.0 6 23.8 pg/ml in men and 34.6 6 44.4 pg/ml in women), whereas those in patients with cardiovascular disease, ST elevation myocardial infarction, or unstable angina range from 574.84 to 710.52 pg/ml (31)(32)(33)(34). We used CCK-8 to assess the effects of IL-10 (0-2000 ng/ml) on the proliferation of hBMSCs for 3 d. As shown in Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In a selfstimulating loop, the microglia can also secrete IL-12, activating NK and stimulating T cells 32 . Conversely, IL-10 is a multifunctional immune cytokine with anti-angiogenic properties 33,34 . Finally, cytokines like IL-1β and TNF-α can suppress tumors via stimulation of cell-mediated humoral immune reaction 35 .…”
Section: Discussionmentioning
confidence: 99%